Features of triamyl citrate synthesis - A. D. Shiryaeva; S. V. Moiseeva; S. V. Levanova; I. L. Glazko (Тонкие химические технологии)
Objectives. To find an effective way for obtaining triamyl citrate, an environmentally friendly, biodegradable citric acid ester used as a plasticizer for PVC-based polymer compositions.Methods. The possibilities of heterogeneous catalysis were analyzed using the case study of three commercial samples of macroporous sulfocationites (Amberlyst™ 15, Amberlyst™ 70, and TULSION® 66). Homogeneous catalysis was studied using the example of orthophosphoric acid (H3PO4), while self-catalysis was investigated during esterification of citric acid with amyl alcohol (ROH). The syntheses were carried out under identical conditions: T = 110 °C, the ratio of CA:ROH = 1:5 (mol) amount of catalyst 1 wt % on the reaction mass in a thermostatically controlled reactor of ideal mixing with continuous distillation of the resulting water.Results. It was found that in all variants (even under self-catalysis conditions), the conversion of citric acid in 180 min reached 94–99%. Triamyl citrate was formed after 9 h with a yield of 90% only when using a homogeneous catalyst (H3PO4) and in the presence of a heterogeneous catalyst sample (Amberlyst ™ 15).Conclusions. The revealed differences in the reactivity of the studied sulfocationites (Amberlyst™ 15, Amberlyst ™ 70, and TULSION® 66) confirm the well-known theoretical positions, according to which the kinetic pseudo-homogeneous model of the esterification process of hydroxy acids in excess of aliphatic alcohols is based on the law of acting masses and depends on the specific surface area of the catalyst, which for Amberlyst ™ 15 is of the greatest importance as compared to Amberlyst ™ 70 and TULSION® 66 (m2/g): 53:36:35, respectively.